Inheritances and the accumulation of wealth in the Eurozone - Stefan Humer; Mathias Moser; Matthias Schnetzer (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper empirically compares the contribution of the two major wealth accumulation factors - earned income and inheritances - to the within country net wealth position of Eurozone households with HFCS data. Using unconditional quantile regressions, we show the varying importance of earned income and inheritances at different parts of the per country distributions and compare them to Eurozone averages. The elasticities of both wealth sources are overly non-linear and display an inverted "U" shape pattern. Around the median household, an additional percentile in the income distribution corresponds to an increase in the net wealth distribution of as much as 0:5 percentiles, while an additional percentile in the inheritance distribution yields up to 1:3 percentiles. At the bottom of the wealth distribution, households have to climb less than two percentiles in the income distribution to compensate a one percentile increase in the inheritance distribution, whereas this ratio surges to almost four percentiles at the top tail and varies distinctively between different countries. These results emphasize the relative importance of inheritances versus income from employment for private wealth creation and question common perceptions of meritocracy.
Keywords: C21; D31; 330; Wealth distribution; household structure